Inhaled Antibiotics for the Prevention of Respiratory Tract Infections in Children With a Tracheostomy - Jutras, Camille; Autmizguine, Julie; Chomton, Maryline; Marquis, Christopher; Nguyen, The Thanh-Diem; Roumeliotis, Nadia; Emeriaud, Guillaume (Frontiers in Pediatrics, 2021)
Objective: To describe the use of prophylactic inhaled antibiotics in children with a tracheostomy and assess if its use is associated with a reduction in exposition to broad-spectrum antibiotics and a lower risk of acquired respiratory tract infections. Methods: A case series study was performed in a tertiary care university affiliated hospital. All consecutive children (<18 years old) with a tracheostomy, hospitalized between January 2004 and November 2016, and treated with prophylactic inhaled antibiotics were identified. We analyzed the 3 month- period before and after initiation of prophylactic inhaled antibiotics and described exposure to broad spectrum antibiotics, the number of respiratory tract infections and the associated adverse events. Results: Six children (median age: 11 months, range: 8–100) were included. One received colimycin, 3 received tobramycin and 2 were treated with both antibiotics in alternance. The median duration of treatment was 74 days (22–173) with one patient still being treated at the end of the study. Patients were exposed to systemic antibiotics for 18 days (2–49) in the 3 months preceding the treatment vs. 2 days (0–15) in the 3 months following the treatment initiation (p = 0.115). The number of respiratory tract infections went from median of 2 (0–3) to 1 (0–1) during the same periods (p = 0.07). Adverse events most commonly reported were cough (n = 2) and increased respiratory secretions post-inhalation (n = 4). Only one new bacterial resistance was observed. Conclusions: This series of consecutive cases underlines the need for future studies evaluating the potential benefit of prophylactic inhaled antibiotics in children with a tracheostomy.